Comparison of the morphology of the anterior cruciate ligament and related bony structures between pigs and humans - Shi, Qinyi; Wang, Huizhi; He, Kaixin; Tao, Mingzhu; Cheng, Cheng-Kung (Frontiers in Veterinary Science, 2022)
Pigs are widely used for clinical research on the anterior cruciate ligament (ACL) because of the similarity of the knee structure to the human knee. But evidence to support the suitability of using porcine samples to guide clinical practices is limited. This study aims to explore the qualitative and quantitative morphological features of the porcine knee and ACL, and to compare these with data on humans reported in literature. 19 porcine knees were used for this study. The bone structures were measured on coronal X-ray images. The length of the ACL was measured using a caliper. The ACL bone insertion sites were marked and measured on a digital photograph. The lengths of the long and short axis of the ACL isthmus were measured on the X-ray microscopy reconstructed images. The outcomes were compared with previously reported data on humans using an abstract independent-samples T test. Qualitative observation indicated a similar location, orientation and general morphology of the porcine ACL to human ACLs. The major difference was the location of the ACL tibial insertion with respect to the anterior horn of the lateral meniscus (AHLM). The porcine ACL was split into AM and PL bundles by the AHLM, while the AHLM was adjacent to the anterolateral border of the ACL tibial insertion in human knees. The quantitative comparison showed no significant difference between the human and porcine ACL in terms of the length of the ACL, the width of the femoral condyle and tibial plateau, and the tibial interspinal width. However, the CSA, the lengths of the long and short axis of the ACL isthmus, and the femoral and tibial insertion areas of the porcine ACL were all significantly larger than the reported features in human knees. Generally, the location, orientation and morphology of the porcine ACL and knee are similar to humans. However, the two-bundle structure is more distinct in a porcine ACL, and the dimensions of the porcine ACL are generally larger. This study may provide useful information to researchers when assessing the feasibility and limitations of using porcine samples for research on the human ACL and knee.